Effects of Rewards Management on Employee Productivity: Case Study Kakira Sugar Limited Kakira Jinja - Gerald Wanyama (Uganda Christian University, 2024)
The study established the relationship between rewards management and employee productivity at KSL. The objectives were; to establish the effects of financial benefits on employee productivity, to determine the role of intrinsic rewards on productivity and to determine how management support influences employee productivity in Kakira Sugar Limited. the study adopted a research design where quantitative method was used to enable in data collection. The study findings indicated that there is a strong statistically significant relationship between rewards management and employee productivity. In the study it was concluded that rewards do play a greater role in productivity since most respondents gave insights that rewards contributed a lot on their productivity in KSL. The study does recommend that the company of KSL should continuously use the rewards management system if in case it wants to either improve or maintain the productivity since employees become motivated once rendered with the rewards whether financial or non-financial but it is very good once it is combined that is to say total rewards.